Thrombocytopenia in solid tumors: Prognostic significance - Majid Ghanavat; Mina Ebrahimi; Hassan Rafieemehr; Mahmood Maniati; Masumeh Maleki Behzad; Saeid Shahrabi (Frontiers Media S.A., 2019)
Solid tumors are a heterogeneous group of malignancies that result from out-of-control proliferation of cells. Thrombocytopenia is a common complication among patients with solid tumors that predispose them to bleeding disorders. The aim of this review article is to investigate the underlying mechanisms of the risk and incidence of thrombocytopenia in solid tumors. It can be argued that thrombocytopenia is a poor prognostic factor in solid tumors that can result from several factors such as polymorphism and mutation in some transcription factors and cytokines involved in megakaryocytic maturation or from the adverse effects of treatment. Therefore, an understanding of the exact mechanism of thrombocytopenia pathogenesis in each stage of solid tumors can help in developing therapeutic strategies to decrease bleeding complications in these malignancies.